ECONOMIC AND LEGAL ASPECTS OF ENSURING THE EFFECTIVENESS OF COUNTERACTING CORRUPTION IN THE SYSTEM OF ANTI-CORRUPTION MEASURES OF STATE AUTHORITIES - Mariia Blikhar; Mariia Vinichuk; Maryana Kashchuk; Vitalii Gapchich; Sergii Babii (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The purpose of the article is to study the theoretical foundations and practical aspects of the economic and legal regulation of the process of ensuring the effectiveness of counteracting corruption in the system of anti-corruption measures of state authorities. The results of the conducted research allow us to assert that corruption is one of the most serious problems of our time, which has emerged acutely in Ukraine, and its scale threatens the sustainable socio-economic and socio-political development of the country and successful integration into the European Union. It is determined that the essence of corruption consists in the commission of deliberate illegal acts by officials, aimed at the use of official powers for personal gain and enrichment. It is established that the existing system of prevention and counteraction to corruption in Ukraine is not able to restrain the rapid pace of its spread, and the main anti-corruption measures are characterized by a low level of effectiveness. The imperfection and weakness of the normative and legal regulation of the processes of prevention and counteraction to corruption in Ukraine by state authorities are revealed. It is found that the highest anti-corruption effectiveness indicators in 2022 were recorded for the activities of the President and the Office of the President of Ukraine, as well as the Security Service of Ukraine, and the lowest for the activities of the Cabinet of Ministers of Ukraine. Strategic guidelines for increasing the effectiveness of counteracting corruption in Ukraine are proposed, among which the primary importance belongs to the activation of the processes of implementation of the anti-corruption reform; normalization of the main aspects of interaction between state authorities and the public in the field of counteracting corruption; development and approval of the Methodology for assessing the level of corruption in Ukraine.